Learning by chance: Investigating gaps in transgender care education amongst family medicine, endocrinology, psychiatry and urology residents - Fung, Raymond; Gallibois, Claire; Coutin, Alexandre; Wright, Sarah (Revue canadienne de l’éducation médicale, 2020)
Background: The transgender (trans) population is one of the most underserved in health care. Not only do they face discrimination and stigma from society as a whole, they also have difficulty accessing transition-related care, leading to adverse outcomes such as suicide. We aimed to increase understanding on how our current postgraduate education system contributes to a lack of care for trans patients. Methods: Our study consisted of 11 semi-structured interviews conducted in 2016 with residents in the following specialties: family medicine (3), endocrinology (3), psychiatry (3), and urology (2). We used Framework Analysis to qualitatively analyze our data. Results: Residents described a lack of trans care education in the core curriculum, in part due to a lack of exposure to experts in this area. They also expressed discomfort when dealing with trans patients, due to inexperience and lack of knowledge. Furthermore, residents in each specialty had false assumptions that other specialties had sufficient knowledge and expertise in trans care. Discussion: This study highlights how the lack of teaching and clinical experiences with trans patients during residency contributes to the poor access to healthcare. By systematically embedding trans care in the curriculum, medical education can play a prominent role in addressing the healthcare disparities of this underserved population.